Konsep Hermeneutika Al-Qur’an Ma’nā-Cum-Mağza dan Aplikasinya dalam Memahami Bunga Bank - Zaman, Akhmad Roja Badrus (SUHUF, 2021)
This article elaborates the theory of ma’nā-cum-maġza and its implementation on the topic of usury in the Qur’an. This paper uses a descriptive-qualitative method, and is included in the library research. The working technique of ma’nā-cum-maġza hermeneutics theory is to do linguistic analysis, to see the historicity of the decline of a verse in macro and micro contexts, and to examine the “maqṣad” or maġza (signification) of a verse. By using this theory, it can be seen that in its historical aspect, usury refers to the phenomenon of the reality of the 7th century Arabs which doubled the nominal amount of the initial loan which led to exploitative and unjust acts. This is different from the concept of bank interest in the contemporary banking system. It is by taking maġza through historical studies, the theory of interpretation of ma’nā-cum-maġza tends to emphasize the moral aspect of the prohibition of usury, and subordinates the legal form of usury—because it has unspeakable legal significance, thus it has made it not expected.